2022
DOI: 10.1111/cas.15384
|View full text |Cite
|
Sign up to set email alerts
|

The HOXC‐AS2/miR‐876‐5p/HKDC1 axis regulates endometrial cancer progression in a high glucose‐related tumor microenvironment

Abstract: The tumor microenvironment (TME) is related to chronic inflammation and is currently identified as a risk factor for the occurrence and development of endometrial cancer (EC). Pyroptosis is a new proinflammatory form of programmed cell death that plays a critical role in the progression of multiple diseases. However, the important role of pyroptosis in high‐glucose (HG)‐related EC and the underlying molecular mechanisms remain elusive. In the present study, transcriptome high‐throughput sequencing revealed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…In vitro experiments showed that overexpression of DRAIR enhanced proliferation and viability of TNBC cells after doxorubicin treatment (99). Accumulated evidence dissected that lncRNA HOXC-AS2 participated in the progression in high glucose-related endometrial cancer (EC) (100). EC patients with diabetes had the increased expression of HKDC1 compared with EC patients with normal glucose.…”
Section: Lncrnas Regulate Glucose Metabolism In Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…In vitro experiments showed that overexpression of DRAIR enhanced proliferation and viability of TNBC cells after doxorubicin treatment (99). Accumulated evidence dissected that lncRNA HOXC-AS2 participated in the progression in high glucose-related endometrial cancer (EC) (100). EC patients with diabetes had the increased expression of HKDC1 compared with EC patients with normal glucose.…”
Section: Lncrnas Regulate Glucose Metabolism In Cancermentioning
confidence: 99%
“…Accumulated evidence dissected that lncRNA HOXC-AS2 participated in the progression in high glucose-related endometrial cancer (EC) ( 100 ). EC patients with diabetes had the increased expression of HKDC1 compared with EC patients with normal glucose.…”
Section: Lncrnas Regulate Glucose Metabolism In Cancermentioning
confidence: 99%
See 3 more Smart Citations